New data on glass sponges (Porifera, Hexactinellida) of the northern Mid-Atlantic Ridge. Part 2. Aphrocallistidae, Euretidae, Euplectellidae and Rossellidae (with descriptions of two new species of Sympagella) - Tabachnick, K.R.; Menshenina, L.L. (Marine Biology Research, 2013)
Species of hexactinellid sponges (families Aphrocallistidae, Euretidae, Euplectellidae, and Rossellidae) collected on the ECOMARexpeditions of the RRS James Cook to the northern Mid-Atlantic Ridge are considered. Two species new to science of the genus Sympagella (Rossellidae, Lanuguinellinae) are described: S. cooki sp. nov. has as a unique feature the absence of discoidal and onychoidal outer ends in microscleres; Sympagella ecomari sp. nov. has the only types of microscleres represented by plumicomes and spicules with discoidal outer ends.Anew name, Bathydorus levis pseudospinosus, is suggested for Bathydorus levis spinosus Wilson, 1904 (junior homonym) to avoid homonymy with Bathydorus spinosus Schulze, 1886 (senior homonym).